Advanced structural neuroimaging in progressive supranuclear palsy: Where do we stand?. (March 2017) - Stezin, Albert; Lenka, Abhishek; Jhunjhunwala, Ketan; Saini, Jitender; Pal, Pramod K.
Abstract: Progressive supranuclear palsy (PSP) is a progressive neurological disorder characterized by presence of supranuclear gaze palsy, early postural instability, parkinsonism and cognitive impairment. Advanced structural neuroimaging studies have demonstrated variable areas of grey and white matter involvement in PSP. Grey matter (GM) involvement is predominantly reported in the midbrain, subcortical structures such as thalamus and basal ganglia, and cerebellum. Most white matter (WM) tracts are also reported to be damaged in PSP. This review analyzes the published studies that have utilized advanced structural imaging techniques such as voxel based morphometry (VBM), diffusion tensor and diffusion weighted imaging (DTI, DWI), magnetic resonance volumetry (MRV), shape analysis, cortical thickness analysis and magnetic resonance morphometry in understanding the in vivo pathological changes in PSP and also discusses their clinical significance. Highlights: Progressive supranuclear palsy (PSP) is a neurodegenerative parkinsonian syndrome. Morphometry, VBM, DTI, volumetry, shape analysis and cortical thickness studies in PSP were reviewed. A total of 63 studies were included in this review. Atrophy and volume loss was present mainly in the frontal cortex and most subcortical structures. White matter changes were more in the corpus callosum and infratentorial structures.